Determination of Electrochemical Kinetic Property for Mixed Ionic Electronic Conductors from Electrical Conductivity Relaxation Measurements. Issue 9 (11th June 2015) - He, Fei; Jin, Xinfang; Tian, Tingfang; Ding, Hanping; Green, Robert D.; Xue, Xingjian
Abstract : Electrical conductivity relaxation (ECR) technique has been widely used to determine surface exchange and bulk diffusion coefficients for mixed ionic electronic conductors (MIECs). However, this extensively employed method is built upon an analytic solution with the form of infinite series derived from a strictly specified geometric sample shape. This may cause various problems for accurate parameter estimation due to the ill-posed nature. This research reports a new strategy to overcome these issues by utilizing a direct numerical method with inverse algorithm solution. The similarity relation between dimensionless relaxation time and chemical Biot number is revealed and used to identify whether or not the electrochemical kinetic property is limited by either bulk diffusion or surface exchange process for a set of MIECs. The Biot number effect on parameter estimation results is systematically studied and a suitable range of Biot number is suggested for obtaining more accurate estimations. The uncertainty induced by measurement noise is also discussed for the estimated parameters. A case study of ECR measurement is carried out for an electrode material (La0.6 Sr0.4 )0.95 Fe0.9 Mo0.1 O3 in CO/CO2 atmosphere at different temperatures and is comprehensively evaluated using the developed approach.